HIV‐1 Vpr inhibits autophagy during the early steps of infection of CD4 T cells. (30th October 2019) - Alfaisal, Jamal; Machado, Alice; Galais, Mathilde; Robert‐Hebmann, Véronique; Arnauné‐Pelloquin, Laetitia; Espert, Lucile; Biard‐Piechaczyk, Martine
Abstract : Background information: Autophagy is induced during HIV‐1 entry into CD4 T cells by the fusion of the membranes triggered by the gp41 envelope glycoprotein. This anti‐HIV‐1 mechanism is inhibited by the viral infectivity factor (Vif) neosynthesized after HIV‐1 integration to allow viral replication. However, autophagy is very rapidly controlled after HIV‐1 entry by a still unknown mechanism. As HIV‐1 viral protein R (Vpr) is the only auxiliary protein found within the virion in substantial amount, we studied its capability to control the early steps of HIV‐1 envelope‐mediated autophagy. Results: We demonstrated that ectopic Vpr inhibits autophagy in both the Jurkat CD4 T cell line and HEK.293T cells. Interestingly, Vpr coming from the virus also blocks autophagy in CD4 T cells, the main cell target of HIV‐1. Furthermore, Vpr decreases the expression level of two essential autophagy proteins (ATG), LC3B and Beclin‐1, and an important autophagy‐related protein, BNIP3 as well as the level of their mRNA. We also demonstrated in HEK.293T cells that Vpr degrades the FOXO3a transcription factor through the ubiquitin proteasome system. Conclusion: Vpr, the only well‐expressed HIV‐1 auxiliary protein incorporated into viruses, is able to negatively control autophagy induced during HIV‐1 entry into CD4 T cells. Significance: We provide insights of how HIV‐1 controls autophagy very early after its entry into CD4 T cells and discovered a new function of Vpr. These results open the route to a better understanding of the roles of Vpr during HIV‐1 infection through FOXO3a degradation and could be important to consider additional therapies that counteract the role of Vpr on autophagy. Abstract : Research article : Autophagy is rapidly induced during HIV‐1 entry. Vpr coming from the HIV‐1 viral particle triggers the proteasomal degradation of FOXO3a, a transcription on many ATG genes, including LC3, Beclin 1 and BNIP3. Thus, during the first step of infection, incoming Vpr, by acting on FOXO3a, induces a dramatic decrease in the expression of these essential ATGs. As a consequence, Vpr blocks the virus‐induced autophagy.